Book Review: Pengantar Perjanjian Lama 1: Taurat dan Sejarah - Ferdi Yunan; Kristianto, Adi Kurnia (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Introduction to the Old Testament 1 by William Sanford Lasor is one of the classic textbooks discussing the Old Testament in the Christian Bible. This book provides readers with a deep understanding of the historical, cultural, and theological context behind the Old Testament books. Lasor uses a strong academic approach in analyzing Old Testament texts. He investigates the historical and cultural contexts in which these texts appear, helping readers understand the messages they contain. Although the book examines ancient texts, Lasor also draws connections between Old Testament messages and contemporary life. This helps readers see how the messages are still relevant in a modern context.